Preparation method of long-service-life doped tungsten bar

By adding dopant and composite surfactant to the preparation process of doped tungsten strips, using layered filling and multi-point filling pressing methods, combining high-temperature sintering and pickling treatment, and covering the surface with alumina film, the problem of easy oxidation and short service life of doped tungsten strips at high temperatures is solved, and high density and high-temperature oxidation resistance are improved.

CN119525508AActive Publication Date: 2025-02-28GANZHOU GRAND SEA W & MO GRP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510082616.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-02-28
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The existing doped tungsten strips are prone to oxidation at high temperatures, have short service life, and have poor density uniformity in complex shapes, making them prone to cracking.

Method used

Dopants and composite surfactants are added to the blue tungsten oxide and high-energy ball milling is carried out. After hydrogen is reduced, combined binder is added. Layered filling and multi-point filling are used for pressing. High-temperature sintering and pickling are carried out in stages. Finally, the surface of the semi-finished product is coated with an alumina film.

Benefits of technology

By increasing the density and high-temperature oxidation resistance of doped tungsten strips, it extends its service life, improves wear resistance and high-temperature oxidation resistance, and reduces porosity and deformation and cracking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of metallurgical processing, in particular to a preparation method of a long-service-life doped tungsten bar. The problem that an existing tungsten bar is short in service life is solved. The preparation method comprises the following steps: adding a doping material and a composite surfactant into blue tungsten oxide, uniformly mixing, adding a combined binder after hydrogen reduction, carrying out layered pressing in a layered filling and multi-point filling manner to obtain a green body, and carrying out high-temperature sintering and acid pickling in stages; and coating aluminum oxide on the surface of the pickled semi-finished product by taking trimethylaluminum and oxygen as raw materials to obtain the long-service-life doped tungsten bar. The density and high-temperature oxidation resistance of the doped tungsten bar are improved by changing the adding amount of blue tungsten oxide, the component proportion of the doping material and the adding amount of the doping material, the combined binder and the composite surfactant and adjusting the pressure of each time of pressing, the temperature and time of different stages of high-temperature sintering and the deposition temperature and time during aluminum oxide coating; and the effect of prolonging the service life of the doped tungsten bar is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metallurgical processing, and in particular to a method for preparing a long-life doped tungsten bar. Background Art

[0002] Doped tungsten bars play a key role in the lighting and heating industries. In the process of electric arc furnace, melting furnace, glass melting furnace, electron beam welding, vacuum melting and casting, the working temperature of doped tungsten bars reaches above 1500℃. In order to ensure that the doped tungsten bars can still maintain a low oxidation rate during long-term high-temperature operation, they need to have excellent high-temperature oxidation resistance to achieve the effect of extending the service life and reducing the cost of use. In order to improve the high-temperature oxidation resistance of doped tungsten bars, the traditional preparation method is to add doping elements to tungsten oxide, and then prepare doped tungsten powder through hydrogen reduction, acid leaching and other steps, and finally obtain doped tungsten bars through pressing and vertical melting sintering. Among them, the mixing uniformity and bonding degree between tungsten oxide as a raw material and the doping material will affect the density of the obtained doped tungsten bars, and then affect the high-temperature oxidation resistance. Generally speaking, a higher density can provide better high-temperature oxidation resistance. In the above application scenarios, the shapes of tungsten bars include strips, rods, plates, blocks and meshes in addition to strips and rods. The ordinary pressing method has poor density uniformity when preparing tungsten bars of complex shapes. The fired tungsten bars are prone to cracking and oxidation at high temperatures. The doped tungsten bars prepared by vertical melting sintering have limited improvement in oxidation resistance at high temperatures and cannot effectively increase their service life. The medium frequency sintering technology can achieve uniform heating inside the material and has a precise temperature control device that can accurately control the temperature during the sintering process, reducing the risk of overburning or underburning. It has the characteristics of high efficiency, energy saving and environmental protection.

[0003] In order to prolong the service life of doped tungsten bars, a method for preparing doped tungsten bars with high service life is proposed. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a doped tungsten bar with a long service life. The present invention overcomes the problem of short service life of existing tungsten bars. After adding doping materials and composite surfactants to blue tungsten oxide and mixing them evenly, a composite binder is added after hydrogen reduction, and layered pressing is performed by layered filling and multi-point filling to obtain a green body, and then high-temperature sintering and pickling are performed in stages; trimethylaluminum and oxygen are used as raw materials to coat the surface of the semi-finished product after pickling with alumina to obtain a long-life doped tungsten bar. The present invention improves the density and high-temperature oxidation resistance of the doped tungsten bar by changing the addition amount of blue tungsten oxide, the component ratio of the doping material, the addition amount of the doping material, the composite binder and the composite surfactant, adjusting the pressure of each pressing, the temperature and time of different stages of high-temperature sintering, and the deposition temperature and time when coating alumina, thereby achieving the effect of extending the service life of the doped tungsten bar.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A method for preparing a long-life doped tungsten bar, in parts by mass, comprises the following steps:

[0007] S1: 95.2-98.6 parts of blue tungsten oxide, 2.6-4.8 parts of doping material and 0.23-0.59 parts of composite surfactant are mixed and subjected to high-energy ball milling for 30 minutes to obtain doped tungsten oxide; the doping material is silicon dioxide, aluminum oxide, potassium oxide and rare earth element oxide; the rare earth element oxide is lanthanum oxide;

[0008] S2 preheats the doped tungsten oxide at 400°C for 3h, then heats it to 900-1100°C at 10°C / min in a hydrogen atmosphere for reduction for 3h, slowly cools it, and then adds 1.1-2.7 parts of a combined binder to granulate to obtain doped tungsten particles;

[0009] S3: filling the doped tungsten particles into the container by layered filling and multi-point filling, and forming the doped tungsten bar green body by cold isostatic pressing; placing the doped tungsten bar green body into a medium frequency sintering furnace for high temperature sintering to obtain a sintered doped tungsten bar semi-finished product, and then washing it with a mixed acid solution after cooling in the furnace, and then washing it with deionized water and ethanol solvent and drying it to obtain the acid-washed doped tungsten bar semi-finished product;

[0010] S4 uses vapor deposition to cover the surface of the acid-washed doped tungsten semi-finished product with an aluminum oxide film to obtain a high-life doped tungsten bar.

[0011] Preferably, the doping material is a mixture of silicon dioxide, aluminum oxide, potassium oxide and lanthanum oxide in a ratio of 0.8:0.6-2.7:0.85:1.2 in parts by mass.

[0012] Preferably, the composite surfactant is obtained by mixing polyethylene glycol and 3-aminopropyltriethoxysilane in a mass ratio of 3.1:2.3.

[0013] Preferably, the combined binder is a mixture of paraffin wax and stearic acid in a mass ratio of 7.4:2.8.

[0014] Preferably, the operating steps of combining layered filling and multi-point filling are as follows: fill 1 / 3 of the mass of the doped tungsten particles for the first time: fill 1 / 15 of the mass of the doped tungsten particles at the top, bottom, left, right and center points of the bottom of the container respectively, spread them evenly and compact them with cold isostatic pressing at a pressure of 350-580MPa; fill 1 / 3 of the mass of the doped tungsten particles for the second time, repeat the steps of the first filling, spread them evenly and compact them with cold isostatic pressing at a pressure of 220-470MPa; fill 1 / 3 of the mass of the doped tungsten particles for the third time, repeat the steps of the first filling, spread them evenly and compact them with cold isostatic pressing at a pressure of 130-390MPa.

[0015] Preferably, S3 high temperature sintering is carried out in a hydrogen atmosphere.

[0016] Preferably, S3 high temperature sintering is divided into a preheating stage, a sintering stage and a tempering treatment stage; the heating rate in the preheating stage is 10°C / min, and after heating to 850°C, it is kept warm for 1.5-3.0 hours; the operation of the sintering stage is: after the preheating stage is completed, continue to heat to 1850-2260°C at 8°C / min, and keep warm for 4-12 hours to obtain a sintered tungsten bar; the operation of the tempering treatment stage is: after the sintering stage is completed, the sintered tungsten bar is cooled to 1380°C at 5°C / min, kept warm for 4-8 hours, and cooled to room temperature with the furnace to obtain a sintered doped tungsten bar semi-finished product.

[0017] Preferably, the operation steps of S3 pickling are: soaking the sintered doped tungsten bar semi-finished product in a mixed acid solution for 30 minutes, taking it out and rinsing it with pure water to dry it, so as to obtain the pickled doped tungsten bar semi-finished product; the mixed acid solution is a mixture of nitric acid and hydrofluoric acid in a volume ratio of 6.4:3.6.

[0018] Preferably, the method for covering the aluminum oxide film is as follows: placing the acid-washed doped tungsten bar semi-finished product on the support of the vapor deposition reaction chamber, turning on the heating system after evacuation, the deposition temperature in the vapor deposition reaction chamber is 850-1150°C, introducing aluminum precursor gas and oxygen source gas into the reaction chamber, and the reaction chamber pressure is 5×10 -2 Torr, deposition time is 45-75min; turn off the heating system and let the reaction chamber cool naturally to room temperature to obtain a high-life doped tungsten bar.

[0019] Preferably, the aluminum precursor gas is trimethylaluminum, and the flow rate of trimethylaluminum is 50 cm 3 / min; oxygen source gas is oxygen, and the oxygen flow rate is 150cm 3 / min.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. Silica, potassium oxide, aluminum oxide and rare earth element oxides are used as additives for preparing high-life doped tungsten bars, which have an important influence on the antioxidant properties of doped tungsten bars. They can reduce the melting point of tungsten, improve thermal stability and density of tungsten bars, save energy, and improve wear resistance and high-temperature antioxidant properties, thereby extending the life of doped tungsten bars. Alumina and lanthanum oxide will form a composite oxide lanthanum aluminate, which will play a role in grain boundary strengthening in doped tungsten bars. At high temperatures, aluminum oxide and silica react to form an aluminum silicate phase, which promotes the densification process of doped tungsten bars. It can be used as a liquid phase to promote the bonding between particles, which helps to eliminate pores during the sintering process. The aluminum silicate phase can also reduce the sintering temperature of doped tungsten bars, thereby reducing energy consumption and shortening sintering time. The addition of surfactants can make the doping material evenly distributed in the system, avoid agglomeration, and make the aluminum silicate phase and lanthanum aluminate evenly distributed. By changing the proportion of aluminum oxide in the doping material, the addition amount of blue tungsten oxide, doping material, lanthanum oxide and composite surfactant, the density of the high-life doped tungsten bar is 16.9g / cm 3 , high temperature oxidation weight gain is 20.1g / cm 2 .

[0022] 2. Paraffin wax has good fluidity at room temperature and can serve as a bridge between tungsten powder particles, enhancing the connection between particles and facilitating the molding into doped tungsten bars of the desired shape; stearic acid is a fatty acid that acts as a bond and lubricates, and helps fill the gaps between tungsten powder particles during the pressing process, thereby reducing the porosity of the final product. Paraffin wax and stearic acid can easily volatilize and decompose during the sintering process, promoting the densification process and reducing deformation and cracking. The two complement each other and help to increase the life of the doped tungsten bars. By changing the amount of combined binder added, the density of the high-life doped tungsten bars is 17.2g / cm 3 , no deformation and cracking occurred.

[0023] 3. In the process of pressing doped tungsten particles into green compacts, the doped tungsten particles are filled into the container by layered filling and multi-point filling, and each layer is pressed separately to improve the uniform density of the pressed green compacts with complex shapes. The pressure of each pressing is changed to improve the density of the pressed green compacts. The density of the high-life doped tungsten bars is 17.6g / cm 3 .

[0024] 4. The high-temperature sintering process plays a vital role in the performance of the doped tungsten bar. The present invention is divided into three stages of high-temperature sintering: preheating, sintering and tempering treatment: the preheating stage allows the combined binder to volatilize and decompose; the sintering stage can improve the high-temperature oxidation resistance of the doped tungsten bar; the tempering stage can eliminate the stress in the doped tungsten bar and increase its life. Sintering in a hydrogen atmosphere can remove the carbon black remaining in the binder. By changing the temperature and time of the high-temperature sintering process, the high-temperature oxidation weight gain of the high-life doped tungsten bar is 13.2g / cm 2 .

[0025] 5. Using trimethylaluminum and oxygen as raw materials, the two are reacted by vapor deposition to obtain aluminum oxide, which is coated on the surface of the doped tungsten bar, which can effectively improve the high-temperature oxidation resistance and extend the service life. By changing the heating temperature and deposition time, the high-temperature oxidation rate of the high-life doped tungsten bar is 7.2g / cm 2 . BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a schematic diagram of high temperature oxidation weight gain of Examples 52, 55-63 and Comparative Example 9 of the present invention. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] See also Figure 1 The present invention provides a method for preparing a high-life doped tungsten bar, and the technical solution is as follows:

[0029] The substance information involved in the present invention is as follows:

[0030] Blue tungsten oxide CAS: 1314-35-8; potassium oxide CAS: 12136-45-7; aluminum oxide CAS: 11092-32-3; cerium oxide CAS: 1306-38-3; polyethylene glycol CAS: 25322-68-3; 3-aminopropyltriethoxysilane CAS: 919-30-2; paraffin CAS: 68476-81-3; stearic acid CAS: 57-11-4; hydrogen CAS: 1333-74-0; nitric acid CAS: 7697-37-2; hydrofluoric acid CAS: 7664-39-3; trimethylaluminum CAS: 75-24-1; oxygen CAS: 7782-44-7.

[0031] Example 1

[0032] S1 Silica, aluminum oxide, potassium oxide and lanthanum oxide were mixed in a mass ratio of 0.8:0.6:0.85:1.2 to obtain a doping material; polyethylene glycol and 3-aminopropyltriethoxysilane were mixed in a mass ratio of 3.1:2.3 to obtain a composite surfactant. 95.2 parts of blue tungsten oxide, 2.6 parts of doping material and 0.23 parts of composite surfactant were mixed and high-energy ball milled for 30 minutes to obtain doped tungsten oxide;

[0033] S2: paraffin wax and stearic acid are mixed in a mass ratio of 7.4:2.8 to obtain a composite binder; doped tungsten oxide is preheated at 400°C for 3 hours, then heated to 1050°C at 10°C / min in a hydrogen atmosphere for reduction for 3 hours, and then slowly cooled and 1.1 parts of the composite binder are added to granulate to obtain doped tungsten particles;

[0034] S3 fills the doped tungsten particles into the container by layered filling and multi-point filling. The first filling is 1 / 3 of the mass of the doped tungsten particles: 1 / 15 of the mass of the doped tungsten particles are filled at the top, bottom, left, right and center points of the bottom of the container respectively, and after spreading evenly, they are compacted by cold isostatic pressing at a pressure of 350MPa; the second filling is 1 / 3 of the mass of the doped tungsten particles, and the steps of the first filling are repeated. After spreading evenly, they are compacted by cold isostatic pressing at a pressure of 220MPa; the third filling is 1 / 3 of the mass of the doped tungsten particles, and the steps of the first filling are repeated. After spreading evenly, they are compacted by cold isostatic pressing at a pressure of 130MPa.

[0035] The doped tungsten bar green body is placed in a medium frequency sintering furnace and sintered at high temperature in a hydrogen atmosphere. The high temperature sintering is divided into a preheating stage, a sintering stage and a tempering treatment stage. The heating rate in the preheating stage is 10℃ / min, and the temperature is kept at 850℃ for 1.5h. The operation in the sintering stage is as follows: after the preheating stage, the temperature is continued to be raised to 1850℃ at 8℃ / min, and the temperature is kept for 4h to obtain a sintered tungsten bar. The operation in the tempering treatment stage is as follows: after the sintering stage, the sintered tungsten bar is cooled to 1380℃ at 5℃ / min, and the temperature is kept for 4h, and the semi-finished sintered doped tungsten bar is obtained by cooling to room temperature with the furnace. Nitric acid and hydrofluoric acid are mixed in a volume ratio of 6.4:3.6 to obtain a mixed acid solution. The semi-finished sintered doped tungsten bar is placed in the mixed acid solution and soaked for 30min, and then taken out and rinsed with pure water to obtain a semi-finished acid-washed doped tungsten bar.

[0036] S4 places the acid-washed doped tungsten semi-finished product on the bracket of the vapor deposition reaction chamber, evacuates the chamber and turns on the heating system, sets the deposition temperature in the reaction chamber to 850°C, introduces trimethylaluminum and oxygen into the reaction chamber, and the trimethylaluminum flow rate is 50cm 3 / min; oxygen flow rate is 150cm 3 / min. The reaction chamber pressure is 5×10 -2Torr, the deposition time is 45 min; the heating system is turned off, and the reaction chamber is allowed to cool naturally to room temperature to obtain a high-life doped tungsten bar.

[0037] Example 2-19

[0038] The reaction parameters and conditions of Example 1 are shown in Table 1.

[0039] Table 1 Reaction parameters and conditions of Examples 1-19

[0040]

[0041] Comparative Example 1

[0042] The reaction parameters and conditions were similar to those of Example 1, except that no alumina was added.

[0043] Comparative Example 2

[0044] The reaction parameters and conditions are the same as those of Example 1, except that no doping material is added.

[0045] Comparative Example 3

[0046] The reaction parameters and conditions are similar to those of Example 1, except that no composite surfactant is added.

[0047] Example 20 Density and High Temperature Oxidation Weight Gain Test

[0048] The high-life doped tungsten bars of Examples 1-19 and Comparative Examples 1-3 were weighed at room temperature using a precision balance for initial weight, and placed in a quartz boat after recording the data. They were then placed in a high-temperature furnace and heated to 1500°C. After the temperature stabilized, timing began, and the atmosphere in the furnace was a pure oxygen atmosphere. After 1 hour, the heating was turned off, and the high-life doped tungsten bars were allowed to cool naturally to room temperature in the furnace. The samples were taken out and weighed after oxidation, and the data was recorded. Calculate the weight gain by oxidation: Calculate the ratio of the weight difference before and after oxidation of each high-life doped tungsten bar to its surface area, i.e., the weight gain by high-temperature oxidation. The density of the high-life doped tungsten bars of Examples 1-19 and Comparative Examples 1-3 was determined by the Archimedean drainage method. The results are shown in Table 2.

[0049] Table 2 Density and high temperature oxidation weight gain of Examples 1-19 and Comparative Examples 1-3

[0050]

[0051] As additives for preparing high-life doped tungsten bars, silicon dioxide, potassium oxide, aluminum oxide and rare earth element oxides will have an important impact on the oxidation resistance of doped tungsten bars. Aluminum oxide can promote the bonding between tungsten particles, improve the overall structural strength and oxidation resistance of doped tungsten bars, and enhance the structural performance and oxidation resistance of tungsten bars by changing the sintering behavior of tungsten powder, thereby improving the overall performance and life of doped tungsten bars; at the same time, the doping of aluminum oxide can improve the density of doped tungsten bars, so that the density of the obtained doped tungsten bars is improved. As shown in Table 1 and Table 2, in Examples 1-5, the proportion of aluminum oxide in the doping material is increased, and the density and high-temperature oxidation resistance of the obtained high-life doped tungsten bars are improved. Silicon dioxide plays a role in stabilizing and improving the material properties during the preparation process, and improves the stability and life of doped tungsten bars in high temperature environments by enhancing the structural performance and oxidation resistance of doped tungsten bars. The addition of potassium oxide can improve the high-temperature deformation performance. Before hydrogen reduction of tungsten, the addition of potassium oxide can improve the stability of doped tungsten bars in high temperature environments and reduce sagging and deformation caused by thermal expansion and other reasons. In a high-temperature environment, the addition of lanthanum oxide can reduce the growth rate of the oxide film on the surface of the doped tungsten bar, and inhibit the generation of oxidation reactions by changing the oxidation kinetics, thereby improving the high-temperature oxidation resistance of the doped tungsten bar. Aluminum oxide and lanthanum oxide will form a composite oxide lanthanum aluminate, which will play a role in grain boundary strengthening in the doped tungsten bar; at high temperatures, aluminum oxide and silicon dioxide react to form an aluminum silicate phase, which promotes the densification process of the doped tungsten bar, and can be used as a liquid phase to promote the bonding between particles, which helps to eliminate pores during the sintering process. The aluminum silicate phase can also reduce the sintering temperature of the doped tungsten bar, thereby reducing energy consumption and shortening the sintering time. In Examples 6-9, by increasing the amount of doping material added to increase the amount of silicon dioxide, potassium oxide and lanthanum oxide added, the density of the high-life doped tungsten bar obtained is increased, and the weight gain of high-temperature oxidation is reduced, indicating that the improvement of high-temperature oxidation resistance helps to extend the service life. The more blue tungsten oxide is added, the greater the purity of tungsten in the product, and the better the high-temperature resistance. In Examples 10-14, increasing the amount of blue tungsten oxide added helps to improve the density of the high-life doped tungsten bars. While increasing the density, the high-temperature oxidation resistance is also improved. Polyethylene glycol and 3-aminopropyltriethoxysilane are used as surfactants to improve the dispersibility of the doping material, so that the aluminum silicate phase and lanthanum aluminate are evenly distributed, and the agglomeration of the components is avoided. In Examples 15-19, increasing the amount of composite surfactant added improves the overall uniformity of the doped tungsten bars obtained, which helps each component to fully play its role. In Example 18, the mass ratio of silicon dioxide, aluminum oxide, potassium oxide, and lanthanum oxide in the doping material is 0.8:2.1:0.85:1.2; the amount of doping material added is 4.3 parts by mass; the amount of blue tungsten oxide added is 98.0 parts by mass; the amount of composite surfactant added is 0.53 parts by mass, and the obtained high-life doped tungsten bar has the best performance and a density of 16.9g / cm3 , high temperature oxidation weight gain 20.1mg / cm 2 In Comparative Example 1, the density of the high-life doped tungsten bar without adding alumina was 15.5 g / cm 3 , high temperature oxidation weight gain 34.8mg / cm 2 In Comparative Example 2, the density of the high-life doped tungsten bar made without adding doping material is 14.1 g / cm 3 , high temperature oxidation weight gain 40.1mg / cm 2 In comparative example 3, no composite surfactant was added, and the density of the obtained high-life doped tungsten rod was 15.8 g / cm 3 , high temperature oxidation weight gain 38.2mg / cm 3 .

[0052] Examples 21-24

[0053] Referring to the reaction parameters and conditions of Example 18, the differences are shown in Table 3.

[0054] Comparative Example 4

[0055] The reaction parameters and conditions were similar to those of Example 18, except that stearic acid was not added.

[0056] Comparative Example 5

[0057] The reaction parameters and conditions were similar to those of Example 18, except that no combination binder was added.

[0058] Example 25 Density Test and Appearance Performance

[0059] The density of the high-life doped tungsten bars of Examples 18, 21-24, and Comparative Examples 4-5 was measured by the Archimedean drainage method and the appearance was observed. The results are shown in Table 3.

[0060] Table 3 Density and appearance of Examples 18, 21-24, and Comparative Examples 4-5

[0061]

[0062] During the preparation process, the roles of paraffin wax and stearic acid complement each other. Pressing stage: Paraffin wax has good fluidity at room temperature. As a bridge between tungsten powder particles, it strengthens the connection between particles, reduces the friction between tungsten powder, and makes tungsten powder easier to flow and evenly distribute during the pressing process, which helps to form a uniform green body. Stearic acid can be used as a binder to help the powder particles better combine. High-temperature sintering stage: The volatilization of paraffin wax may lead to the formation of pores, and the liquid phase produced by the decomposition of stearic acid helps the sintering and densification of tungsten particles and reduces pores. In summary, paraffin wax and stearic acid affect the pressing and sintering behavior of powder during the preparation of doped tungsten bars, thereby improving the density and appearance of doped tungsten bars to extend their service life. As shown in Table 3, the appropriate amount of combined binder added can improve density and appearance; in Example 23, 2.3 parts by mass of combined binder were added, and the density of the obtained high-life doped tungsten bars was 17.2 g / cm 3 , without deformation and cracking. However, paraffin wax will volatilize during the sintering process. If the volatilization is incomplete or excessive, it may leave pores inside the doped tungsten rod, thereby reducing the density and causing defects on the surface of the doped tungsten rod after sintering. As shown in Comparative Example 4, no stearic acid is added, and paraffin wax is used for bonding. The density of the high-life doped tungsten rod is 15.8g / cm 3 , slightly deformed and cracked; in Comparative Example 5, no combined binder was added, and the density of the obtained high-life doped tungsten bar was 15.4g / cm 3 , deformation and cracking occur.

[0063] Examples 26-38

[0064] Referring to the reaction parameters and conditions of Example 23, the differences are shown in Table 4.

[0065] Comparative Example 6

[0066] Refer to the parameters and conditions in Example 23, except that the doped tungsten particles are filled in one time, flattened, and then cold isostatically pressed at a pressure of 550 MPa to obtain a tungsten bar green body.

[0067] Example 39 Density Test

[0068] The density of the high-life doped tungsten bars of Examples 23, 26-38 and Comparative Example 6 was measured by the Archimedean drainage method, and the data was recorded. The results are shown in Table 4.

[0069] Table 4 Density of Examples 23, 26-38, and Comparative Example 6

[0070]

[0071] Multi-layer and multi-point filling and pressing can help improve the density uniformity of the doped tungsten bars, because the pressure of each layer can be controlled individually, so as to achieve a more uniform density distribution in the entire volume. Higher density usually leads to better mechanical properties. By precisely controlling the pressing pressure, multi-layer and multi-point filling can produce tungsten bars with higher density, which helps to increase the service life of the doped tungsten bars. At the same time, uniform pressing can lead to a more uniform grain structure, thereby affecting the sintering behavior and final performance of the doped tungsten bars. A higher pressure is usually required during the first filling to ensure good densification of the bottom powder, which helps the stability of the entire pressed body. As shown in Table 4, in Examples 23, 26-29, the pressing pressure of the first filling was increased, and the density of the doped tungsten bars showed an upward trend. In Example 28, when the first pressing pressure was 530 MPa, the density of the high-life doped tungsten bars obtained was 17.3 g / cm 3 The pressure of the middle layer is slightly lower than that of the bottom layer, because the bottom layer has provided a stable support. In Examples 29-34, the second pressing pressure is 220-470 MPa. In Example 33, when the second pressing pressure is 420 MPa, the density of the obtained high-life doped tungsten bar is 17.5 g / cm 3 The top layer only needs to ensure the densification of the top layer powder, and does not need to provide support like the bottom layer. The pressure is between 130-390MPa. In Example 37, the third filling and pressing pressure is 330MPa, and the density of the obtained high-life doped tungsten rod is 17.6g / cm 3 In the comparative example, the tungsten bar green body was prepared by the one-time filling and pressing method, which resulted in poor pressing effect. The density of the obtained high-life doped tungsten bar was 16.1g / cm 3 .

[0072] Examples 40-53

[0073] Referring to the reaction parameters and conditions of Example 37, the differences are shown in Table 5.

[0074] Comparative Example 7

[0075] The reaction parameters and conditions are similar to those of Example 37, except that the doped tungsten green bars are not subjected to a preheating stage.

[0076] Comparative Example 8

[0077] The reaction parameters and conditions are the same as those of Example 37, except that the sintered tungsten rod is not subjected to the tempering stage.

[0078] Example 54 High temperature oxidation weight gain test

[0079] The high-life doped tungsten bars of Examples 37, 40-53, and Comparative Examples 7-8 were weighed at room temperature using a precision balance for initial weight, and then placed in a quartz boat after recording the data, and then placed in a high-temperature furnace and heated to 1500°C. After the temperature stabilized, the timing was started, and the atmosphere in the furnace was a pure oxygen atmosphere. After 1 hour, the heating was turned off, and the high-life doped tungsten bars were allowed to cool naturally to room temperature in the furnace. After being taken out, the weight of the sample after oxidation was weighed and the data was recorded. Calculation of oxidation weight gain: Calculate the weight difference before and after oxidation of each high-life doped tungsten bar and the ratio of the surface area, that is, the high-temperature oxidation weight gain, and the results are shown in Table 5.

[0080] Table 5 High temperature oxidation weight gain of Examples 37, 40-53, and Comparative Examples 7-8

[0081]

[0082] The high-temperature sintering process plays a vital role in the performance of the doped tungsten bar. The present invention is divided into three stages of high-temperature sintering: preheating, sintering, and tempering. The preheating stage can make the paraffin stearic acid of the combined binder fully volatilize and decompose. Prolonging the insulation time can allow the bubbles generated by the decomposition in this process to fully overflow, reduce the porosity, make the composition and structure inside the doped tungsten bar more uniform, and improve the density; it can also help the doped tungsten bar material to gradually heat up, reduce the thermal stress caused by temperature mutations, reduce internal defects, avoid cracks in the material during processing, improve high-temperature oxidation resistance, and extend service life. As shown in Table 5, in Examples 37, 40-42, the insulation time in the preheating stage is extended, and the high-temperature oxidation weight gain of the obtained high-life doped tungsten bar is reduced; in Example 41, when the preheating stage is kept for 2.5 hours, the high-temperature oxidation weight gain of the obtained high-life doped tungsten bar is 16.7 mg / cm 2 In Comparative Example 7, the green body of the doped tungsten bar was not subjected to the preheating stage, and the high-life doped tungsten bar obtained had a high-temperature oxidation weight gain of 24.1 mg / cm 2 . The temperature and holding time in the sintering stage are also important factors affecting high-temperature oxidation resistance. Appropriate sintering temperature and time can optimize the mechanical properties and thermal stability of the doped tungsten rod, and improve the high-temperature oxidation resistance of the doped tungsten rod; the temperature and time during the sintering process affect the size and shape of the grains, thereby affecting the microstructure and comprehensive performance of the material. The longer the sintering time, the higher the degree of densification the material can achieve. However, too long sintering time may cause excessive grain growth and reduce mechanical properties. In Examples 43-51, the temperature and time of the sintering stage were adjusted to improve the high-temperature oxidation resistance of the high-life doped tungsten rods obtained; in Example 50, the sintering stage temperature was 2260°C, the holding time was 10h, and the high-temperature oxidation weight gain of the high-life doped tungsten rods obtained was 14.0mg / cm 2The tempering stage can eliminate the internal stress of the doped tungsten rod and prevent cracking due to stress concentration during use. In Example 52, the holding time of the tempering stage is 6 hours, and the high-temperature oxidation weight gain of the obtained high-life doped tungsten rod is 13.2 mg / cm 2 In Comparative Example 8, the sintered tungsten rod was not subjected to the tempering stage, and the high-life doped tungsten rod obtained had a high-temperature oxidation weight gain of 25.9 mg / cm 2 .

[0083] Examples 55-63

[0084] Referring to the reaction parameters and conditions of Example 52, the differences are shown in Table 6.

[0085] Comparative Example 9

[0086] The reaction parameters and conditions were the same as those of Example 52, except that no alumina coating was performed.

[0087] Example 64 High temperature oxidation weight gain test

[0088] The high-life doped tungsten bars of Examples 52, 55-63, and Comparative Example 9 were weighed at room temperature using a precision balance for initial weight, and then placed in a quartz boat after recording the data. They were then placed in a high-temperature furnace and heated to 1500°C. After the temperature stabilized, the timing was started. The atmosphere in the furnace was pure oxygen. After 1 hour, the heating was turned off, and the high-life doped tungsten bars were allowed to cool naturally to room temperature in the furnace. After being taken out, the weight of the sample after oxidation was weighed and the data was recorded. Calculation of oxidation weight gain: Calculate the ratio of the weight difference before and after oxidation of each high-life doped tungsten bar to the surface area, that is, the high-temperature oxidation weight gain. The results are shown in Tables 6 and Figure 1 shown.

[0089] Table 6 High temperature oxidation weight gain of Examples 52, 55-63 and Comparative Example 9

[0090]

[0091] Trimethylaluminum can react with oxygen to form aluminum oxide, which is deposited on the surface of the tungsten bar to increase its high-temperature oxidation resistance. When depositing aluminum oxide film on tungsten bar, deposition temperature and time are two key parameters, which have a significant impact on the performance of the final product. Higher deposition temperature is conducive to the crystallization of aluminum oxide film, forming a film with a good crystal structure, so that the prepared doped tungsten bar has better thermal stability, which helps to improve high-temperature oxidation resistance and extend service life. Lower temperatures may lead to the formation of amorphous or microcrystalline structures, which may reduce the hardness and thermal stability of the film. However, too high a temperature may cause a mismatch in the thermal expansion coefficient between the aluminum oxide film and the tungsten substrate, resulting in greater thermal stress, excessive interface reaction between the aluminum oxide and the tungsten substrate, forming a fragile interface layer, reducing adhesion, and causing the film to crack or fall off. As shown in Table 6 and Figure 1 As shown in the figure, in Examples 52, 55-60, the high temperature oxidation weight gain of the obtained high life doped tungsten strips is gradually reduced by increasing the deposition temperature. In Example 59, when the deposition temperature is 1100°C, the high temperature oxidation weight gain of the obtained high life doped tungsten strips is 9.6 mg / cm 2 The deposition time affects the concentration and reaction degree of the gas in the reaction chamber, and thus affects the growth rate and final structure of the film. Prolonging the deposition time helps to improve the uniformity of the film, increase the thickness of aluminum oxide, and improve its antioxidant properties and mechanical protection. In Example 62, the deposition time was 65 minutes, and the high-temperature oxidation weight gain of the obtained high-life doped tungsten strip was 7.2 mg / cm 2 In Comparative Example 9, no aluminum oxide coating was performed, and the high-life doped tungsten strip had a high-temperature oxidation weight gain of 16.9 mg / cm 2 .

[0092] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a long-life doped tungsten bar, characterized in that: The method for preparing the long-life doped tungsten bar comprises the following steps, measured in parts by mass: S1: 95.2-98.6 parts of blue tungsten oxide, 2.6-4.8 parts of doping material and 0.23-0.59 parts of composite surfactant are mixed, and high-energy ball milling is performed for 30 minutes to obtain doped tungsten oxide; the doping material is a mixture of silicon dioxide, aluminum oxide, potassium oxide and rare earth element oxide; the rare earth element oxide is lanthanum oxide; S2: preheating the doped tungsten oxide at 400° C. for 3 h, then heating to 1050° C. at 10° C. / min in a hydrogen atmosphere, reducing for 3 h, slowly cooling, adding 1.1-2.7 parts of a combined binder to granulate to obtain doped tungsten particles; S3: filling the doped tungsten particles into a container by layered filling and multi-point filling, and forming the doped tungsten bar green body by cold isostatic pressing; placing the doped tungsten bar green body into a medium frequency sintering furnace for high temperature sintering to obtain a sintered doped tungsten bar semi-finished product, and washing it with a mixed acid solution after cooling in the furnace, and then washing it with deionized water and ethanol solvent and drying it to obtain the acid-washed doped tungsten bar semi-finished product; S4 uses a vapor deposition method to cover the surface of the acid-washed doped tungsten bar semi-finished product with an aluminum oxide film to obtain the high-life doped tungsten bar.

2. The method for preparing a long-life doped tungsten bar according to claim 1, characterized in that: In parts by mass, the doping material is a mixture of silicon dioxide, aluminum oxide, potassium oxide and lanthanum oxide in a ratio of 0.8:0.6-2.7:0.85:1.

2.

3. The method for preparing a long-life doped tungsten bar according to claim 1, characterized in that: The composite surfactant is obtained by mixing polyethylene glycol and 3-aminopropyltriethoxysilane in a mass ratio of 3.1:2.

3.

4. The method for preparing a long-life doped tungsten bar according to claim 1, characterized in that: The combined binder is obtained by mixing paraffin wax and stearic acid in a mass ratio of 7.4:2.

8.

5. The method for preparing a long-life doped tungsten bar according to claim 1, characterized in that: The operation steps of combining layered filling and multi-point filling are as follows: fill 1 / 3 of the mass of the doped tungsten particles for the first time, fill 1 / 15 of the mass of the doped tungsten particles at the top, bottom, left, right and center points of the bottom of the container respectively, spread them evenly and compact them with the cold isostatic press at a pressure of 350-580MPa; fill 1 / 3 of the mass of the doped tungsten particles for the second time, repeat the steps of the first filling, spread them evenly and compact them with the cold isostatic press at a pressure of 220-470MPa; fill 1 / 3 of the mass of the doped tungsten particles for the third time, repeat the steps of the first filling, spread them evenly and compact them with the cold isostatic press at a pressure of 130-390MPa.

6. The method for preparing a long-life doped tungsten bar according to claim 1, characterized in that: The high temperature sintering in S3 is carried out in a hydrogen atmosphere.

7. The method for preparing a long-life doped tungsten bar according to claim 1, characterized in that: S3 The high temperature sintering is divided into a preheating stage, a sintering stage and a tempering treatment stage; the heating rate in the preheating stage is 10℃ / min, and after heating to 850℃, it is kept warm for 1.5-3.0h; the operation of the sintering stage is: after the preheating stage is completed, continue to heat to 1850-2260℃ at 8℃ / min, and keep warm for 4-12h to obtain the sintered tungsten bar; the operation of the tempering treatment stage is: after the sintering stage is completed, the sintered tungsten bar is cooled to 1380℃ at 5℃ / min, kept warm for 4-8h, and cooled to room temperature with the furnace to obtain the sintered doped tungsten bar semi-finished product.

8. The method for preparing a long-life doped tungsten bar according to claim 1, characterized in that: The pickling operation steps in S3 are: putting the sintered doped tungsten bar semi-finished product into the mixed acid solution and soaking it for 30 minutes, taking it out and rinsing it with pure water to dry it, so as to obtain the pickled doped tungsten bar semi-finished product; the mixed acid solution is obtained by mixing nitric acid and hydrofluoric acid in a volume ratio of 6.4:3.

6.

9. The method for preparing a long-life doped tungsten bar according to claim 1, characterized in that: The method for covering the aluminum oxide film is as follows: placing the acid-washed doped tungsten bar semi-finished product on a support in a vapor deposition reaction chamber, evacuating the chamber and turning on the heating system, wherein the deposition temperature in the vapor deposition reaction chamber is 850-1150° C., introducing aluminum precursor gas and oxygen source gas into the reaction chamber, and the reaction chamber pressure is 5×10 -2 Torr, the deposition time is 45-75 min; the heating system is turned off, and the reaction chamber is allowed to cool naturally to room temperature to obtain the high-life doped tungsten strip.

10. The method for preparing a long-life doped tungsten bar according to claim 9, characterized in that: The aluminum precursor gas is trimethylaluminum, and the flow rate of trimethylaluminum is 50cm 3 / min; the oxygen source gas is oxygen, and the oxygen flow rate is 150cm 3 / min.

Citation Information

Patent Citations

  • Preparation method for micro-lanthanum-doped tungsten wire

    CN102424941A

  • Production method of stirrer for rare earth doped smelting metal

    CN112251622A

  • Production process of high-performance doped tungsten bar

    CN116352100A

  • Method of producing metallic tungsten bar by acid washing and doping tungsten powder

    CN1475590A

  • High density tungsten material sintered at low temperature

    WO2001000892A1